Anthropocentric Symbols in Where the Wild Things Are by Maurice Sendak - Regga Navratilova Ariyanto; Rahayu Puji Haryanti (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The purpose of this study is to analyze the anthropocentric symbols present in the children's storybook "Where the Wild Things Are" by Maurice Sendak. To explain these symbols, the semiotic theory proposed by Roland Barthes is employed in this study, which explains them through three levels: denotative, connotative, and mythical meanings. This study uses a qualitative research method and a descriptive approach that focuses on the images and words contained in the children's storybook entitled Where the Wild Things Are by Maurice Sendak. The results of this study indicate that the anthropocentric symbols contained in the children's story entitled Where the Wild Things Are by Maurice Sendak have appeared since the beginning of the story, namely since the transformation of Max's bedroom into a forest to Max's exploration of the forest that grew in his room until he was crowned "King of all wild things". These symbols have strengthened the ideological myth that humans are superior and destined to dominate nature.